If it's not what You are looking for type in the equation solver your own equation and let us solve it.
30=3(-2x)
We move all terms to the left:
30-(3(-2x))=0
We calculate terms in parentheses: -(3(-2x)), so:We get rid of parentheses
3(-2x)
We multiply parentheses
-6x
Back to the equation:
-(-6x)
6x+30=0
We move all terms containing x to the left, all other terms to the right
6x=-30
x=-30/6
x=-5
| 4(n+7)=52 | | 39x^2+4x-4=0 | | 2x+1=1/3x+5 | | 6u+8=28 | | −5x+0=−18 | | 21=3-3s | | 6+4(3-k)=3(-2k+9) | | 2x+1=1/3+5 | | 6x+12=8N | | 4(2x+2)=56 | | 5f+6=31 | | −5x=−18 | | 2+34(x-5)=5 | | 4/7(21/8x+0.5)=-2(1/7-5/28) | | 1/4=4x-3 | | 5(y+2/5=-3 | | 4^x=85 | | k^2+8k-12=48 | | 6-4x=6x=8x+4 | | 2t^2-16t+40=20 | | 50=-5(v-9) | | 54=3(r-70) | | 50=-5(v–9) | | 54=4(r-70) | | 13-u/2=14 | | x*3/5=2/5 | | 13–u2=14 | | (3x+15)+(2x+35)=180 | | (2^n)-1=10 | | x+3/5=2/5 | | 5x+2+6x+3=50 | | 2^n - 1=10 |